IDENTIFICATION OF CMV INFECTION IN INFLAMMATORY BOWEL DISEASE-WHAT TEST IS BEST?. (8th June 2013) - Kalansooriya, V; Loughrey, M; Feeney, S; Coyle, P; McCaughey, C; Turner, G
Abstract : Introduction: There is uncertainty in the significance of CMV infection in exacerbations of Inflammatory Bowel Disease (IBD). As methods for determining the presence of CMV in inflamed mucosa improve, varying degrees of specificity and sensitivity make interpretation crucial. Aims/Background: To assess the significance of known markers of CMV in the setting of IBD and to determine the best combination for identifying active infection. Method: Blood PCR / IgM / IgG, faecal PCR, biopsy PCR and histology results were analyzed in samples received from July 2009 to 2012 at the Regional Virology Laboratory. Results: Of 110 samples received, 14 were repeated samples leaving 96 patient episodes. 17 were positive out of 19 patients tested for IgG. Patients with negative IgG were negative for all other markers. Where there was a positive PCR /histology and IgG was tested, it was positive in all cases. See table 1 Of the 96, 28 were positive for one/more of 6 modalities tested see table 2 Conclusion: Tissue PCR has the highest sensitivity. Overall, the incidence of CMV infection in this group was 29%. A negative IgG was associated with negative results for all other forms of testing while all confirmed active CMV episodes had positive IgG. Further study of the clinical significance of CMV in IBD is required.